The Effect of Facilities and Infrastructure, and Standard Operating Procedures on Public Satisfaction, Mediated By The Quality of Public Services - Eka Hartati Ningsih; M. Zahari; Mufidah (Greenation International Journal of Tourism and Management, 2025)
The facilities and infrastructure, standard operating procedures, public service quality, and public satisfaction are all intended to be described in this study. Additionally, it examines how standard operating procedures, infrastructure, and facilities affect public satisfaction. Additionally, it examines how infrastructure, facilities, and standard operating procedures affect public satisfaction by measuring the quality of public services. The Population and Civil Registration Office of the West Tanjung Jabung Regency in Jambi Province served as the study's site. Both principal and supplemental data were used in this investigation. Out of the 73,266 service users who comprised the study's population, a random sample of 100 respondents was selected. This study used a survey methodology that included both descriptive and quantitative analysis. Path Analysis with a Partial Least Squares (PLS) method was employed for the quantitative analysis. The outcomes demonstrated that public satisfaction was positively and considerably impacted by infrastructure and standard operating procedures. Public satisfaction is impacted by infrastructure and standard operating procedures through the caliber of public services. These findings show that the public's perception of service quality increases with improved infrastructure and standard operating procedures. The key to fulfilling the public's expectations of government services is optimal service quality. As a result, the presence of government representatives will provide the public with observable advantages, leading to increased satisfaction levels.